Involvement of Coenzyme Q10 in Various Neurodegenerative and Psychiatric Diseases - Alireza Ebrahimi; Amirhossein Kamyab; Sahar Hosseini; Sedigheh Ebrahimi; Soheil Ashkani-Esfahani (Biochemistry Research International)
Coenzyme Q10 (CoQ10), commonly known as ubiquinone, is a vitamin-like component generated in mitochondrial inner membranes. This molecule is detected broadly in different parts of the human body in various quantities. This molecule can be absorbed by the digestive system from various nutritional sources as supplements. CoQ10 exists in three states: in a of reduced form (ubiquinol), in a semiquinone radical form, and in oxidized ubiquinone form in different organs of the body, playing a crucial role in electron transportation and contributing to energy metabolism and oxygen utilization, especially in the musculoskeletal and nervous systems. Since the early 1980s, research about CoQ10 has become the interest for two reasons. First, CoQ10 deficiency has been found to have a link with cardiovascular, neurologic, and cancer disorders. Second, this molecule has an antioxidant and free-radical scavenger nature. Since then, several investigations have indicated that the drug may benefit patients with cardiovascular, neuromuscular, and neurodegenerative illnesses. CoQ10 may protect the neurological system from degeneration and degradation due to its antioxidant and energy-regulating activity in mitochondria. This agent has shown its efficacy in preventing and treating neurological diseases such as migraine, Parkinson’s disease, Alzheimer’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and Friedreich’s ataxia. This study reviews the literature to highlight this agent’s potential therapeutic effects in the mentioned neurological disorders.